POTENSI STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING (PBL), READING QUESTIONING AND ANSWERING (RQA) DAN KOMBINASI MEMBERDAYAKAN KARAKTER SISWA PUTRA DAN PUTRI SMAN KOTA MALANG PADA PEMBELAJARAN BIOLOGI - Putri Octa Hadiyanti; Aloysius Duran Corebima; Abdul Ghofur (Graduate School of Universitas Negeri Malang, 2016)
The aims of this research were to investigate: 1) The effect of Problem Based Learning (PBL), Reading Questioning and Answering (RQA), and PBL integrated with RQA learning (PBL+RQA) on students’ characters, 2) The effects of gender on students' characters, and 3) the effect of the interaction between learning strategies and gender on students’ characters. The population of this research was all the tenth grade students of state senior high schools in Malang. The results showed that 1) There was not any effect of biology learning strategies on the students’ characters. 2) There was an effect of gender on the students’ characters. The average of the characters of the female students was 2,81% higher than that of the male students. 3) There was no interaction effect of learning strategy and gender on the students’ characters.Penelitian ini bertujuan mengkaji: 1) Pengaruh strategi pembelajaran Problem Based Learning (PBL), Reading Questioning and Answering (RQA), dan PBL dipadu RQA terhadap karakter siswa, 2) Pengaruh gender terhadap pembentukkan karakter siswa, dan 3) Pengaruh interaksi strategi pembelajaran dan gender terhadap karakter siswa. Populasi penelitian ialah seluruh siswa kelas X SMAN Malang. Hasil penelitian menunjukkan hal-hal berikut. 1) Tidak ada pengaruh strategi pembelajaran terhadap karakter siswa. 2) Perbedaan gender berpengaruh terhadap pembentukkan karakter siswa. Nilai rerata terkoreksi karakter siswa putri lebih tinggi 2,81% dari siswa putra. 3) Interaksi strategi pembelajaran dan gender tidak berpengaruh terhadap pembentukkan karakter siswa.